Significance of photosystem integrity and reducing Cd accumulation in mitigating Cd stress on olive tree inoculated with soil-borne bacteria consortium is variety-dependent - Rabaa Hidri; Rahma Azri; Katja Burow; Walid Zorrig; Ahmed Debez; Nouf M. Alyami; Mokded Rabhi; Asma Bensalem-Fnayou; Ahmed Mliki; Philipp Franken; Ricardo Aroca (Plant Stress)
Rhizosphere microbial community role in boosting fruit tree ability to cope with heavy metals is gaining interest. Here, we address the effects of in-frame holobiont microbial inoculation on two Tunisian olive tree varieties (Olea europaea L. cv. Chemlali and Chetoui) exposed to CdCl2 for one month. Shoot Cd content, leaf pigment contents, chlorophyll fluorescence, and energy conversion-related traits in photosystems I and II (PSI and PSII) were considered. Following pyrosequencing-based 16S rRNA analysis, Proteobacteria, and to a lesser extent Firmicutes phylums, were the most abundant. Both Cd-treated olive varieties showed a significant decrease in leaf pigment contents, however, this depressive effect was significantly mitigated following inoculation. PSI and PSII activities were more altered in Cd-treated Chetoui as compared to Chemlali. Quantum yield and electron transport of PSI and PSII were also more impacted in Chetoui, whereas the limitation of the donor side of PSI increased in the latter. Yet, Cd impact on these parameters was significantly reduced in inoculated plants. The quantum yield of nonregulated non-photochemical energy loss in PSII significantly increased in both olive varieties under Cd stress, but values were markedly restored with inoculation. High Cd accumulation observed in Chetoui shoots upon Cd exposure was significantly lower in inoculated plants. Overall, the consortium used improved olive tree Cd tolerance likely due to the restoration of leaf pigment contents and the better integrity of photosystems in both varieties, whereas lowering Cd translocation to shoots would be more prominent in Chetoui. Long-term experiments will be conducted to confirm these results.